Pengabdian Masyarakat Pemilihan Alat Kontrasepsi Di Desa Babakan Asem Teluk Naga Tangerang - Ariana Widyastuti; Christina Sudaryanti; Romauli Magdalena; Febi Ratnasari; Anita Trisnawati As’yat (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Population explosion is one of the main problems in Indonesia. In 2021 the total population of Indonesia is 273,879,750 people, there is an increase of 2,529,861 people compared to 2020. One of the efforts made by the central government to suppress the rate of population growth is to create a Family Planning Village program or more often called KB Village. The purpose of this community service is to provide the community with knowledge about the selection of contraceptives. The method used is lecture, demonstration and interactive question and answer. The target of this counseling is 20 people of PUS (fertile age couples). Extension activities were carried out in Kedung Jaya Village, RT 01/RW05, Babakan Asem Village, Teluk Naga District. The stages of outreach activities began with greeting, explaining the purpose of counseling, conducting counseling by explaining materials about choosing contraceptives and introducing the types of contraceptives, as well as demonstrations of the installation of IUDs and implants. After that, it was followed by interactive question and answer, evaluation and closed by saying thank you to all participants. The results of the evaluation of the extension activities showed that the knowledge of the participants had increased, this could be seen from the percentage of participants' answers to the questionnaire that had been given a positive increase in each indicator. The conclusion is that the extension activities run smoothly according to the plans that have been made.